Model Radio Dakwah dalam Meningkatkan Pemahaman Keagamaan Masyarakat - Syarif Fauzi; Afief Abd. Latief (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2016)
This paper discusses the radio model of da'wah and the characteristics of radio da'wah seen from da’wah unit and its role in increasing religious understanding of audience. The object of research is Radio Fajri 99.3 FM Bogor. This research uses descriptive method with qualitative approach. Radio Fajri as a propagation radio is very important role in the development of da'wah and with the aim of improving the religious understanding of society in Bogor. Radio Fajri from its inception was influenced by technological developments, quality broadcast programs, and public interest in Islamic broadcasting. Radio Fajri is instrumental in the da'wah of Islam and the progress of religious understanding of society in Bogor. The propagation of da'wah can be successful because this radio departs from the consciousness of its founders who want the community to easily obtain information about Islam. Tulisan ini menggambarkan model dan karakteristik radio dakwah dilihat dari unsur dakwah dalam program siarannya dan peranannya dalam meningkatkan pemahaman keagamaan masyarakat. Objek penelitian Radio Fajri 99,3 FM Bogor. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Radio Fajri sebagai radio dakwah sangat berperan penting dalam perkembangan dakwah dan dengan tujuan meningkatkan pemahaman keagamaan masyarakat di Bogor. Radio Fajri dari awal didirikan ikut dipengaruhi oleh perkembangan teknologi, program siaran yang berkualitas, dan minat masyarakat pada siaran Islami. Radio Fajri sangat berperan dalam dakwah Islam dan kemajuan perkembangan pemahaman keagamaan masyarakat di Bogor. Penyebaran dakwah bisa sukses karena radio ini berangkat dari kesadaran pendirinya yang menginginkan agar masyarakat mudah dalam mendapatkan informasi tentang Islam.